Medulloblastoma in a toddler with Gorlin syndrome. Issue 2 (3rd April 2018) - Al-Rahawan, Mohamad G.; Trevino, Sorleen; Jacob, Roy; Murray, Jeffrey C.; Al-Rahawan, Mohamad M.
ABSTRACT: Gorlin syndrome (GS) is a rare hereditary multisystem disorder caused by mutations in PTCH1, PTCH2, or SUFU . It is characterized by multiple anomalies and an increased risk of developing various tumors. Basal cell carcinoma is most common, and medulloblastoma (MB) is especially frequent in patients with SUFU mutations. MB treatment often includes radiation therapy in patients older than 3 years; however, such treatment is very toxic to patients with GS. Most reported cases of MB in patients with GS present after GS is diagnosed. We report a male toddler with multicentric posterior fossa tumor and calcifications along the falx cerebri, suggesting MB and GS. Pathology revealed nodular MB. His testing confirmed a germline SUFU mutation. His tumor resolved with three induction cycles of chemotherapy, but he died of respiratory failure due to infection at 20 months of age. Overlooking calcifications along the falx cerebri in children with MB can induce significant morbidity.